1999
DOI: 10.1007/s002280050577
|View full text |Cite
|
Sign up to set email alerts
|

The oral bioavailability of pentosan polysulphate sodium in healthy volunteers

Abstract: The oral bioavailability of PPS is negligible in young healthy males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Taken together, these results indicate that oral PPS does not have anticoagulant activity following oral administration, nor does it affect warfarin pharmacokinetics. Previous studies have shown that PPS has a low oral bioavailability and that anticoagulant activity is notable only following injection 9 . Thus, it is not surprising that the pharmacodynamics of warfarin are not affected upon coadministration of oral warfarin and pentosan polysulfate sodium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Taken together, these results indicate that oral PPS does not have anticoagulant activity following oral administration, nor does it affect warfarin pharmacokinetics. Previous studies have shown that PPS has a low oral bioavailability and that anticoagulant activity is notable only following injection 9 . Thus, it is not surprising that the pharmacodynamics of warfarin are not affected upon coadministration of oral warfarin and pentosan polysulfate sodium.…”
Section: Discussionmentioning
confidence: 99%
“…Faaij and colleagues 9 evaluated the oral availability of oral pentosan polysulfate sodium in 18 healthy male subjects with normal coagulation. In their study, subjects received 1500 mg of oral pentosan polysulfate sodium or 50 mg IV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A study of oral pentosan polysulfate administered to 18 healthy volunteers reported negligible bioavailability after a single dose of 1500 mg failed to alter coagulation parameters. 5 Furthermore, trials using oral pentosan polysulfate sodium doses greater than 900 mg/d reported no significant coagulopathies 6,7 and no significant adverse anticoagulation effects were demonstrated in longterm studies (90-119 months) of oral pentosan polysulfate use in interstitial cystitis. 8,9 Despite its limited bioavailability, coagulation monitoring with oral pentosan polysulfate has been suggested.…”
Section: Commentmentioning
confidence: 99%